"Willing but Unwilling": Attitudinal barriers to adoption of home-based health information technology among older adults. (June 2014) - Young, Rachel; Willis, Erin; Cameron, Glen; Geana, Mugur
While much research focuses on adoption of electronic health-care records and other information technology among health-care providers, less research explores patient attitudes. This qualitative study examines barriers to adoption of home-based health information technology, particularly personal electronic health records, among older adults. We conducted in-depth interviews (30–90 min duration) with 35 American adults, aged 46–72 years, to determine their perceptions of and attitudes toward home-based health information technology. Analysis of interview data revealed that most barriers to adoption fell under four themes: technological discomfort, privacy or security concerns, lack of relative advantage, and perceived distance from the user representation. Based on our findings, systems to promote home-based health information technology should incorporate familiar computer applications, alleviate privacy and security concerns, and align with older adults' active and engaged self-image.